KUALIFIKASI INTELEKTUAL DAN MORAL MUFASIR PADA ABAD KONTEMPORER - Nur Afiyah; Eko Zulfikar (Al-Misykah: Jurnal Studi Al-qur'an dan Tafsir, 2022)
Abstract: Not a few Muslims who openly dare to interpret the Qur’an without following the terms and conditions that apply. This paper attempts to examine the limitations of the intellectual and moral qualifications of commentators in interpreting the Qur’an in the contemporary century. By using the descriptive-analytical method and the Qur’anic science approach and interpretation, it is concluded that; first, there are at least five requirements for the intellectual qualifications of the interpreter, namely; know Arabic and the rules of language, the science of rhetoric, and the science of ushul fiqh, know the basics of al-Qur’an science, know science and technology, know the traditions of the Prophet with all kinds of aspects; and know about man with all his character. Second, the ethical and moral qualification requirements for commentators include; have a straight faith, clean from lust, good intentions and right intentions, have good morals, practice the knowledge possessed, be careful in quoting an opinion, have a humble nature, have a noble soul, dare to call for the truth, look good, patient and calm, puts people who are more important than him, and has a mature provision.